2022
DOI: 10.1021/acsanm.2c01966
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy and Domain Structure in Nanoscale-Thick MoS2/CoFeB Heterostructures: Implications for Transition Metal Dichalcogenide-Based Thin Films

Abstract: Transition metal dichalcogenides (TMD) possess properties which makes them potential candidates for various spintronic applications. Heterostructures of TMD with magnetic thin film have been extensively considered for spin−orbital torque, enhancement of perpendicular magnetic anisotropy etc. However, the effect of TMD on magnetic anisotropy in heterostructures of in-plane magnetization has not been studied so far. Further the effect of the TMD on the domain structure and magnetization reversal of the ferromagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…This implies that complete spin angular momentum relaxation occurs within the ML of MoS 2 , which is expected due to high interfacial spin-orbit coupling (ISOC) in the ML of MoS 2 . 69,72,73 A similar phenomenon i.e., complete spin angular momentum relaxation in MLs for TMDs was also reported in previous reports. [15][16][17] This ISOC is also well known to provide the most dominating role in spin relaxation for 2D NM materials.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…This implies that complete spin angular momentum relaxation occurs within the ML of MoS 2 , which is expected due to high interfacial spin-orbit coupling (ISOC) in the ML of MoS 2 . 69,72,73 A similar phenomenon i.e., complete spin angular momentum relaxation in MLs for TMDs was also reported in previous reports. [15][16][17] This ISOC is also well known to provide the most dominating role in spin relaxation for 2D NM materials.…”
Section: Resultssupporting
confidence: 88%
“…The relatively higher value of ∼2.0 mT is observed in μ 0 H k for the samples of both the TMD2 and TMD2A series as compared to that for the case of n L = 0 (where no MoS 2 ). The significant change in anisotropy suggests the influence of the monolayer due to its interfacial exchange coupling 15,69 i.e., changes in the interfacial SOC of MoS 2 / CoFeB heterostructures. Since the main goal of the present study is to analyse magnetic damping and the spin pumping efficiency, the identification of the anisotropy mechanism and its variation as a function of n L is not considered here.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They have attributed the origin of MA to bond-orientational anisotropy due to interface interaction. Thiruvengadam et al grew FeCoB on SiO2 and MoS2 substrate [65]; MA in the case of only FeCoB/MoS2 is observed and attributed to the hybridization between MoS2 and Fe or Co. Our observation related to the asymmetry at FeCoB/MgO and MgO/FeCoB interface is in accordance with the theoretical study, where PMA (perpendicular magnetic anisotropy) was found in FeCoB/MgO/FeCoB structures, driven by FeCoB/MgO interface [1,66].…”
Section: Discussionsupporting
confidence: 91%
“…Other studies also reported an MA in the Co/MoS 2 bilayer due to the crystalline structure of the MoS 2 as the underlying layer 11 . In addition, an MA is shown in the CoFeB/MoS 2 bilayer due to hybridization at the interface 29 . Therefore, the observed in-plane magnetic anisotropy in the Co/WS 2 sample can be attributed to the crystalline structure of the Co layer on WS 2 and hybridization between WS 2 and Co.…”
Section: Resultsmentioning
confidence: 98%